Imagining Law: Essays in Conversation with Judith Gardam - Babie, Paul; Stephens, Dale (University of Adelaide Press, 2016)
By any measure, Judith Gardam has accomplished much in her professional life and is rightly acknowledged by scholars throughout the world as an expert in her many fields of diverse interest - including international law, energy law and feminist theory. This book celebrates her academic life and work with twelve essays from leading scholars in Gardam's fields of expertise.